Взаимосвязи и взаимообусловленности межкультурного образования и коммуникации на иностранном языке - Pacholczyk, Tadeusz (Wydawnictwo Naukowe UAM, 2013)
The contemporary glottodidactics is an interdisciplinary science, which is reflected, among others, in the transition from mono- to bi- and multiculturalism. The main objective of this paper is to define the relationships between, and conditions of, intercultural teaching and foreign language communication. The following issues will be explored in detail: - discussion of the main assumptions of the post-communicative paradigm of contemporary glottodidactics; - definition of the subject of cultural studies and linguistics in the context of the relationships between “language and culture”; - development of relationships in terms of communication and intercultural competence; - definition of the main objective of intercultural communication; - analysis of relationships as well as intercultural teaching and communication based on examples.
Relationships between and conditions of intercultural teaching and foreign language communication
Wzajemne związki i uwarunkowania w kształceniu interkulturowym i komunikacji w języku obcym